What happened to the 'Great American Jobs Machine'? - Richiardi, M; Nolan, B; Kenworthy, L (International Microsimulation Association, 2020)
In the 1980s and 1990s the US employment rate increased steadily, and by 2000 it was one of the highest among the rich democratic nations. Since then it has declined both in absolute terms and relative to other countries. We use an in-depth comparison between the United States and the United Kingdom to probe the causes of America’s poor recent performance. Contrary to a common narrative, a comparative perspective suggests that the decline in US labour force participation is not confined to the (white) male population; the divergence in the female participation rate is even more pronounced. We do not find evidence that the poor US performance is linked to cyclical patterns, such as the 2008–09 Great Recession; instead, it is a more pervasive, longer-run phenomenon. The relative decline of US participation rates compared to the UK is attributable to shifts in socio-demographic characteristics, such as education, and to shifts in the impact of those characteristics, which have become more adverse to participation.